Pengaruh Strategi Guru dalam Memberi Perhatian Terhadap Motivasi Siswa di Madrasah Aliyah Miftahul Ulum Kepuhkembeng Peterongan Jombang - Solichatun Solichatun (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2018)
This study aims to determine the relationship between the teacher's strategy of paying attention to the achievement motivation of class VIII MA Mifatahul Ulum Kepuhkembeng Peterongan Jombang students. The test for the normality of the X variable, namely the teacher's strategy of Chi squared with a significant level of 5%, resulted in Chi squared Count = 17.32, db = 16. Chi squared Table = 26.3 with TS 5%, db = 16. is categorized as normally distributed. In the Y variable, students' achievement motivation Chi squared Count = 24.16 Chi squared Table = 27.6 so that it includes a normal distribution. Hypothesis test F count = 4.098 consulted with F table TS 5%, db 1: 48 is 4.04 so F Count > F Table or 4.098 > 4.04 concluded that there is an influence between Teacher Strategy and Achievement Motivation. So the relationship between variables X and Y by testing r squared / r correlation, it is found that r correlation = 0.079 there is a positive relationship. The amount of the teacher's strategy on student achievement motivation is 100% - 7.9% = 921% while the rest are other external factors.